2002
DOI: 10.1021/ac010875b
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Capillary Electrophoresis Using a Low-Concentration Additive with the Consideration of Relative Mobilities

Abstract: Most affinity studies in capillary electrophoresis assume that the analyte concentration is much smaller than the additive concentration so that the migration of the analyte has no effect on the concentration of the additive in the capillary. However, in most medium-to high-affinity interactions, the additive concentration has to be kept rather low to observe the changes in analyte mobility before saturation is reached. In this paper, a mathematical model is developed to describe the migration behavior of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…A bubble cell capillary was utilized in order to increase detection sensitivity due to the relatively poor UV absorption properties of the BS. It is desirable to keep the sample concentrations in mobility shift ACE as low as possible relative to the ligand concentration [27,[40][41][42][43][44] (to be discussed in Section 3.2). To this end a BS concentration of 5610 26 M was found to be detectable and subsequently used as the sample concentration throughout.…”
Section: Ace Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A bubble cell capillary was utilized in order to increase detection sensitivity due to the relatively poor UV absorption properties of the BS. It is desirable to keep the sample concentrations in mobility shift ACE as low as possible relative to the ligand concentration [27,[40][41][42][43][44] (to be discussed in Section 3.2). To this end a BS concentration of 5610 26 M was found to be detectable and subsequently used as the sample concentration throughout.…”
Section: Ace Proceduresmentioning
confidence: 99%
“…For high affinity interactions other restrictions may apply. In mobility shift ACE experiments, it has been observed that the ligand induced shift in analyte mobility is dependent on the analyte concentration injected [40][41][42][43][44]56]. Consequently, it is generally recommended that a) Stability constants determined by a phase solubility technique (displacement assay) [15].…”
Section: Estimation Of Stability Constantsmentioning
confidence: 99%
“…On the y-axis are reported the mobility shifts of the isoforms N and I 2 of b 2 -m injected in a capillary filled with (A) 50 mM and (B) 100 mM library compound dissolved in the BGE. Mobility shift is defined as the difference between the effective mobility of b 2 -m peaks in neat buffer and in the presence of the additive [43]; each mobility shift value is the average of two replicates. Inset of (A): electropherograms of b 2 -m injected in the BGE and in the BGE added with 50 mM CREMS-05.…”
Section: Ultrafiltration-cementioning
confidence: 99%
“…When in a CE system at a low concentration of protein as additive a steady state is reached, the additive entering the analyte plug is unaffected by the mobility of the additive. However, when a steady state is not reached, the mobility of the analyte plug may be affected by the amount of additive entering the plug and the time required to reach the steady state [82]. In an ACE study of the kedarcidin-chromophoreapoprotein interaction, the addition of organic solvents was found to reduce the hydrogen bond interaction between the protein and the chromophore [1].…”
Section: Protein-small Molecule Interactionmentioning
confidence: 99%